Pljučni hamartom - Blazina, Jerca (Zdravniški vestnik, 2006)
Abstract Background Hamartomas are the most common benign neoplasms of the lung. The population incidence is 2.5/1000. In most cases the diagnosis is based on computed ton`ography (CT) and fine needle aspiration biopsy (FNAB). In this report we reviewed cases of pulyrconary ha martoma seen at Golnik Hospital and studied the diagnostic and therapeutic procedures used in each case. Methods 35 cases diagnosed as pulmonary hamartoma at Golnik Hospital in the last eight years were studied. We reviewed medical records of 30 patients who were hospitalized. We also reviewed the cytologic smears of 31 patients. Results There were 21 females and 14 males, the average age was 60.5 years, the average size of hamartoma was 21.7 mm. For diagnosing hamartoma we used CTand FNAB in 16 (45.7%) patients, only FNAB in 15 (42.9% and only CT in 4 (11..4%) patients. Cytologic smears of all 31 patients contained chondroid substance or mature cartilage, fibromyxoid material was present in 29 (93.5%),adipose cells or tissue in 24 (77.4%) and cuboidal cells in 28 (90.3%)specimens. Over this period 6 (17.1%) patients underwent surgery, the definitive histologic diagnosis in all cases was hamartoma. Conclusions In some cases of pulmonary hamartoma the definitive diagnosis can be made only byCT without invasive diagnostic procedures. ll`lany times CT does not yield adefinitive diagnosis and in these cases we recommend transthoracic FNAB.
Keywords: Biopsija igelna; Biopsy, Needle; Diagnosis; diagnostika; Hamartom; Hamartoma; Lung Diseases; Pathology; Pljuča, bolezni; pljučne bolezni; Therapy; Tomografija radiografska, računalniška; Tomography, X-Ray Computed